Sexual satisfaction and oversexualization among adults. The moderating role of self-esteem - Iwona L. Janicka; Karolina A. Jarecka (Current Issues in Personality Psychology)
Background In the contemporary world, there is excessive creation and exposure of one’s own sexuality among adults. Taking this into account, the determinants of sexualization are being sought. The aim of this research was to assess the significance of selected demographic variables and the number of sexual partners, as well as psychological variables (self-esteem and sexual satisfaction) for revealing behaviours related to over-sexualization. We also investigated whether self-esteem can moderate the relationship between sexual satisfaction and over-sexualization.